2021
DOI: 10.1136/jitc-2021-002503
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals distinct cellular factors for response to immunotherapy targeting CD73 and PD-1 in colorectal cancer

Abstract: BackgroundAlthough cancer immunotherapy is one of the most effective advanced-stage cancer therapies, no clinically approved cancer immunotherapies currently exist for colorectal cancer (CRC). Recently, programmed cell death protein 1 (PD-1) blockade has exhibited clinical benefits according to ongoing clinical trials. However, ongoing clinical trials for cancer immunotherapies are focused on PD-1 signaling inhibitors such as pembrolizumab, nivolumab, and atezolizumab. In this study, we focused on revealing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 52 publications
(48 reference statements)
1
34
0
Order By: Relevance
“…Translationally, targeting BGN represents a possible strategy to reorient TAMs toward the antitumor M1 phenotype. Treg cells are another vital group of immunosuppressive cells that mediate immune tolerance, inhibition of Tregs by targeting pivotal molecules could reverse tumor immunosuppression ( 52 54 ). In our present study, BGN-mediated immunosuppression may also involve Treg cells, which are functionally categorized into nTregs and iTregs ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Translationally, targeting BGN represents a possible strategy to reorient TAMs toward the antitumor M1 phenotype. Treg cells are another vital group of immunosuppressive cells that mediate immune tolerance, inhibition of Tregs by targeting pivotal molecules could reverse tumor immunosuppression ( 52 54 ). In our present study, BGN-mediated immunosuppression may also involve Treg cells, which are functionally categorized into nTregs and iTregs ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…One way to evaluate T cell aging behaviors in CRC patients would be using single-cell RNA sequencing. Current studies provide valuable insights not only on the specific subtypes of exhausted/senescent T cells found in CRC [ 81 , 114 , 115 ], but also on immune cell distribution in colon versus rectal tumors [ 116 ]. Furthermore, using mouse models with progressive aging phenotypes could be an excellent tool to study how aged T cells impact CRC development ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The following data were extracted from the included studies: (1) the first author, (2) the publication year, (3) the country, (4) the sample size, (5) male to female ratio, (6) median age, (7) high tumor stage/low tumor stage ratio, (8) the cancer therapy records of the patients, (9) TIGIT evaluation method, (10) TIGIT antibody ID, (11) the prognostic value of TIGIT immune checkpoint, (12) the clinicopathological significance of TIGIT, (13) the association between TIGIT and PD-1 immune checkpoints, and (14) the prognostic value of TIGIT + CD8 + tumor-infiltrating lymphocytes.…”
Section: Data Extractionmentioning
confidence: 99%
“…Deng et al have shown that CD8 + T-cell subpopulations widely express PD-1, cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), T-cell immunoglobulin mucin-3 (TIM-3), and lymphocyte activation gene-3 (LAG-3), and TIGIT [ 11 ]. Kim et al have indicated that the majority of exhausted CD8 + T-cells highly express CTLA-4, LAG-3, TIGIT, and TIM-3 [ 12 ]. Therefore, other inhibitory immune checkpoint molecules might contribute to maintaining the immunosuppressive tumor microenvironment following monotherapy with monoclonal antibodies targeting one inhibitory axis.…”
Section: Introductionmentioning
confidence: 99%